Is there still a role for digital rectal examination in the prostate cancer diagnostic pathway in the COVID-19 and post COVID-19 era?. (1st January 2021) - Tan, Wei Shen; Wong, Anton; Mahmalji, Wasim; Raza, Asif
Abstract: Digital rectal examination (DRE) is routinely performed as part of a urology clinical assessment in patients with a clinical suspicion of prostate cancer. An abnormal DRE or a raised prostate specific antigen (PSA) level are part of the criteria for primary care referral to secondary care due to a suspicion of prostate cancer. The current Coronavirus-19 (COVID-19) pandemic has resulted in the rapid adoption of virtual consultations in the form of telephone or video consultations making clinical examination difficult. In the case of prostate cancer diagnostic pathways, often clinicians now rely on PSA measurements and MRI, where radiological services are available, without the requirement for a DRE. We discuss the limited role DRE has in the modern prostate cancer diagnostic pathway due to the widespread adoption of MRI particularly in the COVID-19 era.